Editorial 13(4) - de Fatima Aranha de Queiroz e Melo, Maria; Medeiros Marinho dos Santos, Larissa; Rodrigues de Alvarenga Filho, José; Saraiva de Queiroz, Isabela (Revista Pesquisas e Práticas Psicossociais, 2018)
-